Comparative Study Management Of Training (MOT) Between Blended Learning And Fully Online Learning Methods - Susanty, Yunni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2021)
The COVID 19 pandemic also has an impact on the education and training aspects of the State Civil Apparatus. MOT training in Puslatbang PKASN LAN, which was originally carried out by blended learning in 2019, has been changed to fully online learning in 2020, as an effort to reduce the spread of the COVID 19 virus. The purpose of this study is to find out whether there are differences on the learning outcomes between MOT participants in 2019, which attended by 30 people, and MOT participants in 2020, which attended by 25 people. Data processing and analysis techniques in this study using quantitative methods. The statistical test used is the non-parametric statistical test using the Mann Whitney U test. The sampling technique used was total sampling, where all members of the population were used as samples. The results revealed that there was no difference in the learning outcomes of MOT participants between those using the blended learning method and those using the fully online learning method. Based on this information, fully online learning is very possible to be applied. Nevertheless, the Training Institution must pay attention to the availability of facilities and infrastructure that support the learning process electronically. Also, the limited interaction between lecturers and participants when doing online learning should be balanced with the ability of lecturers to convey material with technology-based learning techniques. In this case, the roles of all parties will determine the optimal achievement of the fully online learning process.